2011
DOI: 10.3109/0886022x.2011.585730
|View full text |Cite
|
Sign up to set email alerts
|

An Autopsy Case of Mitochondrial Myopathy, Encephalopathy, Lactic Acidosis, and Stroke-Like Episodes (MELAS) with Intestinal Bleeding in Chronic Renal Failure

Abstract: A 50-year-old man who underwent hemodialysis (HD) at local outpatient HD center due to end-stage renal disease (ESRD) was transferred to our hospital because of pneumonia. He had severe emaciation and past history of congestive heart failure. Presenting symptoms almost consistently involved difficulty in hearing and recurrent attacks of migraine-like headaches. He was diagnosed with dilated cardiomyopathy, showing diastolic mechanical dyssynchrony by tissue Doppler echocardiography. On the day of death, he had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In a 35-year-old female with MELAS syndrome resulting from the m.13513G>A mutation, renal failure was the initial manifestation of the MID 9 years before diagnosis of the MID (10). In a 50-year-old male with MELAS syndrome, chronic renal failure requiring hemodialysis was one of the clinical manifestations (16). Chronic renal failure was the indication for renal transplantation in a 58-year-old male with MELAS syndrome (17).…”
Section: Resultsmentioning
confidence: 99%
“…In a 35-year-old female with MELAS syndrome resulting from the m.13513G>A mutation, renal failure was the initial manifestation of the MID 9 years before diagnosis of the MID (10). In a 50-year-old male with MELAS syndrome, chronic renal failure requiring hemodialysis was one of the clinical manifestations (16). Chronic renal failure was the indication for renal transplantation in a 58-year-old male with MELAS syndrome (17).…”
Section: Resultsmentioning
confidence: 99%
“…Declining renal function impairs the normal physiological mechanisms regulating blood levels of calcium, phosphate, vitamin D, parathyroid hormone, and fibroblast growth factor, which then impact on multi‐organ functions, such as azotemia, hypertension, osteodystrophy, and bleeding under skin and mucosa …”
Section: Introductionmentioning
confidence: 99%
“…Declining renal function impairs the normal physiological mechanisms regulating blood levels of calcium, phosphate, vitamin D, parathyroid hormone, and fibroblast growth factor, 7 which then impact on multi-organ functions, such as azotemia, hypertension, osteodystrophy, and bleeding under skin and mucosa. [8][9][10][11] Kidney disease also negatively affects the status of oral health. Studies showed that hemodialysis (HD) patients had increased accumulation of supragingival plaque and a higher number of missing teeth.…”
Section: Introductionmentioning
confidence: 99%
“…While kidney disease due to mitochondrial point mutations has occasionally been reported in the absence of extrarenal features, 13,23 it more commonly occurs in the setting of MELAS syndrome 14,[24][25][26][27][28] or deafness, which usually occurs with diabetes. 11,12,26,[29][30][31][32][33][34][35] Point mutations that occur in a protein-coding region of mtDNA in association with a kidney phenotype are very rare. 36 A singlebase deletion in the complex I subunit NADH dehydrogenase 5, has been reported to occur in a single individual with glomerulocystic kidney disease and renal failure.…”
mentioning
confidence: 99%